SENAM HIPERTENSI DAN LATIHAN NAPAS DALAM PADA TEKANAN DARAH LANSIA - Suryandari, Dewi; Fadillah, Siti; Safitri, Wahyuningsih (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Hypertension is a medical condition often referred to as a silent killer because it often has no symptoms but can lead to serious complications. One independent nursing intervention that can be implemented to help control blood pressure is hypertension exercises and deep breathing. These interventions are relatively simple and easy to perform, as well as non-pharmacological and natural, so they can be implemented independently by individuals. Objective: To determine the effect of hypertension exercises and deep breathing on systolic and diastolic blood pressure in elderly people with hypertension. Methods: This study was an experimental study with a quasi-experimental design and nonequivalent control group design. The sampling technique used purposive sampling with 18 respondents in one group. Data analysis used univariate and bivariate analysis using paired t-tests for normally distributed data and wilcoxon tests for non-normally distributed data. Results: After hypertension exercise therapy and deep breathing, systolic and diastolic blood pressure were examined. The wilcoxon test results showed systolic blood pressure before and after hypertension exercise and deep breathing (p-value 0.000), diastolic blood pressure before and after hypertension exercise and deep breathing (p-value 0.002). These results indicate that Ho is rejected and Ha is accepted or there is an effect of hypertension exercise and deep breathing on systolic and diastolic blood pressure in elderly with hypertension at the Sibela Mojosongo Community Health Center. Conclusion: There is an effect of hypertension and deep breathing exercises on systolic and diastolic blood pressure in the elderly with hypertension.